MANAJEMEN STRATEGI DALAM MENINGKATKAN MUTU SEKOLAH DI MA NAHDLATUL WATHAN KECAMATAN LICIN BANYUWANGI - Afrida Nur Laili (AT TAMKIN : Jurnal Pengembangan Masyarakat Islam dan Perubahan Sosial, 2021)
This study aims to determine the implementation of strategic management in improving the quality of schools in MA Nahdlatul Wathan, Licin District, Banyuwangi. This study uses a qualitative method with a descriptive approach. Data collection techniques in this study using observation techniques, interviews and documentation. While the data analysis in this study is to use interactive data analysis, namely, data reduction, data presentation and conclusions. The results of this study indicate that the implementation of strategic management by conducting internal analysis and external analysis up to the evaluation stage, in an effort to determine the extent of the success of an institution's achievements. Success in improving the quality of education in madrasas is certainly mutually sustainable with one another. In measuring the quality of madrasas, several things can be known, including the maximum process of teaching and learning activities, adequate facilities, the professionalism of teachers with their respective qualifications, support from various parties, one of which is the community around the madrasa.